Automatic Grading of Scanned Multiple Choice Answer Sheets - Muangprathub, Jirapond; Shichim, Oatchima; Jaroensuk, Yuthaya; Kajornkasirat, Siriwan (International Journal of Engineering and Technology, 2018)
The motivations for automatic grading of image-based multiple choice answer sheets include significant time and cost reductions. The proposed method supports any pencils or pens used on thin papers, as well as low-cost gridded paper that is easy to use in a typical test. Fourteen different scenarios pertaining to 560 answer sheets were evaluated with automatic reporting of the final grading and its summary. The result shows that an average accuracy of 100% for the cases with nearly complete pencil or pen markings. In the cases with incomplete markings, such as small markings, overflow, and deleted or unclean markings, the accuracies were 62.42%, 93.16%, 99.57%, respectively. The proposed system operates 2.5 times faster than the conventional manual method.Â Â